Loop induced H± →w±Z decays in the aligned two-Higgs-doublet model LOOP INDUCED H± →w±Z DECAYS in ⋯ GAUHAR ABBAS, DIGANTA DAS, and MONALISA PATRA - Abbas G.; Das D.; Patra M. (My University, 2025)
We present a complete one-loop computation of the H±→W±Z decay in the aligned two-Higgs-doublet model. The constraints from the electroweak precision observables, perturbative unitarity, vacuum stability, and flavor physics are all taken into account along with the latest Large Hadron Collider searches for the charged Higgs. It is observed that a large enhancement of the branching ratio can be obtained in the limit where there is a large splitting between the charged and pseudoscalar Higgs masses as well as for the largest allowed values of the alignment parameter ςu. We find that the maximum possible branching ratio in the case of a large mass splitting between mH± and mA is ≈10-3 for mH± (200,700) GeV. © 2018 authors. Published by the American Physical Society.